2021
DOI: 10.1002/cm.21697
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of the ubiquitin proteasome system block myofibril assembly in cardiomyocytes derived from chick embryos and human pluripotent stem cells

Abstract: Details of sarcomeric protein assembly during de novo myofibril formation closely resemble myofibrillogenesis in skeletal and cardiac myocytes in birds, rodents, and zebrafish. The arrangement of proteins during myofibrillogenesis follows a three-step process: beginning with premyofibrils, followed by nascent myofibrils, and concluding with mature myofibrils (reviewed in Sanger et al., 2017). Assembly and maintenance of myofibrils in living muscle cells. In: Handbook of experimental pharmacology, 2017 [pp. 39-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…The surprising finding was that some muscle myosin II, but not the nonmuscle myosin II, had to be proteolyzed in the nascent myofibril for the mature myofibril to be formed (Wang et al, 2020). Wang et al (2022) have extended their previous studies on the effects of UPS inhibitors on myofibrillogenesis in skeletal muscle cells (Wang et al, 2020) to both embryonic chick cardiomyocytes and human inducible PSC‐derived cardiomyocytes, and obtained similar results, that is, UPS inhibitors block the formation of mature myofibrils at the nascent myofibril stage.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…The surprising finding was that some muscle myosin II, but not the nonmuscle myosin II, had to be proteolyzed in the nascent myofibril for the mature myofibril to be formed (Wang et al, 2020). Wang et al (2022) have extended their previous studies on the effects of UPS inhibitors on myofibrillogenesis in skeletal muscle cells (Wang et al, 2020) to both embryonic chick cardiomyocytes and human inducible PSC‐derived cardiomyocytes, and obtained similar results, that is, UPS inhibitors block the formation of mature myofibrils at the nascent myofibril stage.…”
Section: Resultsmentioning
confidence: 68%
“…The Z-bodies of the nascent myofibrils become the initial binding sites for the attachment of the N-termini of titin molecules. The bipolar arrangements of titins in the Z-bands are essential for the binding of the bipolar muscle myosin II filaments in mature myofibrils the first cardiomyocytes isolated from quail precardiac mesoderm (Du et al, 2003); formation of myofibrils inside intact embryonic chick hearts (Du, Sanger, & Sanger, 2008); in cultured neonatal mouse cardiomyocytes (White et al, 2018), and now in cardiomyocytes derived from human induced Pluripotent Stem Cells (hiPSCs) (Wang et al, 2022). This three-step model was also supported by experiments in fixed and living skeletal muscle cells (avian muscle cultures, Sanger et al, 2002;Sanger, Mittal, Pochapin, & Sanger, 1986a, 1986bSanger, Sanger, & Franzini-Armstrong, 2004;Sanger, Wang, Fan, White, & Sanger, 2010;Turnacioglu, Mittal, Dabiri, Sanger, & Sanger, 1997a, 1997bTurnacioglu et al, 1996;Ayoob et al, 2000;Wang et al, 2020Wang et al, , 2018Wang et al, , 2007Stout, Wang, Sanger, & Sanger, 2008; in situ embryonic zebrafish, Sanger, Wang, Holloway, Du, & Sanger, 2009; and mouse muscle cultures, White, Barro, Makarenkova, Sanger, & Sanger, 2014).…”
Section: Premyofibrils Contain Only Nonmuscle Myosin II In Minisarcom...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies of sarcomeric protein localization during myofibril assembly in skeletal and cardiac muscle cells (reviewed in Sanger et al, 2005, 2017; White, Barro, Makarenkova, Sanger, & Sanger, 2014; White et al, 2018) led us to propose that premyofibrils and nascent myofibrils are precursors of mature myofibrils (Rhee et al, 1994; Sanger et al, 2017). With FRAP analysis we found that exchange of sarcomeric proteins between a cytoplasmic pool and sarcomere subunits takes place in each myofibril stage, but is more dynamic in the early stages of assembly (premyofibril and nascent myofibril) than in mature myofibrils (Wang et al, 2005, 2007, 2008, 2018, 2020, 2022; Wang, Dube, Mittal, Sanger, & Sanger, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The wt-YFP-α-actin (a) and the H40Y YFP-α-actin (d) exhibit identical recoveries for the plus and minus ends of the actin filaments. The G15R YFP-α-actin (b) and cytochalasin-D treated myotubes expressing wt-YFP-α-actin (d) reveal decreased incorporation of α-actin at the plus ends, and increased recoveries at the minus ends of the thin filaments compared to the wt-YFP-α-actin (a) and H40Y YFP-α-actin (d) in myotubes assembly (premyofibril and nascent myofibril) than in mature myofibrils (Wang et al, 2005(Wang et al, , 2007(Wang et al, , 2008(Wang et al, , 2018(Wang et al, , 2020(Wang et al, , 2022Wang, Dube, Mittal, Sanger, & Sanger, 2011).…”
Section: Discussionmentioning
confidence: 99%